2001
DOI: 10.1097/00006534-200112000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Capsular Response to the Biocell RTV and Mentor 1600 Siltex Breast Implant Surface Texturing: A Scanning Electron Microscopic Study

Abstract: The utility of mammary prosthesis texturing in the prevention of capsular contracture was established some 20 years ago. Various models of implant texturing are currently on the market. We decided to study two of the most popular implants with two different surface texturings: the Biocell RTV and the Mentor 1600 Siltex. An observation at the electron microscopic level of the implants' surfaces was achieved. At the time of a prospective survey on 10 patients, the capsule fragments corresponding to these two pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 29 publications
1
59
0
4
Order By: Relevance
“…The direct contact with the Biocell textured surface, supported by the firmness of the highly cohesive gel, and its engagement with a surgically created vascular host pocket frequently allows for tissue adherence and immobility with softness. 8,19 These findings, first established with Biocell tissue expanders, are more likely to occur with the 410 implant than with less cohesive, round, textured implants in a less precise surgical pocket. Furthermore, the reduced rate of capsular contracture with the Natrelle 410 implant and the clinically appreciated softness has been described as providing a one breast feel as compared with a round implant moving in its larger pocket separate from the movement of the overlying breast and soft tissue.…”
Section: Discussionmentioning
confidence: 97%
“…The direct contact with the Biocell textured surface, supported by the firmness of the highly cohesive gel, and its engagement with a surgically created vascular host pocket frequently allows for tissue adherence and immobility with softness. 8,19 These findings, first established with Biocell tissue expanders, are more likely to occur with the 410 implant than with less cohesive, round, textured implants in a less precise surgical pocket. Furthermore, the reduced rate of capsular contracture with the Natrelle 410 implant and the clinically appreciated softness has been described as providing a one breast feel as compared with a round implant moving in its larger pocket separate from the movement of the overlying breast and soft tissue.…”
Section: Discussionmentioning
confidence: 97%
“…One of the critical issues during the evolution of the texture is to find a way to stabilize the implant in the breast pocket. Studies have demonstrated that the pore size is critical to allow for tissue adherence leading to the "adhesive effect" and implant stabilization (33). However, it was not clear if the pore size correlated with a reduction in capsular contracture, but did correlate with implant stabilization (33).…”
Section: Surfacementioning
confidence: 99%
“…Danino et al compared the BioCell texture with pore diameter of 600-800 μm with a depth of 150-200 μm to Siltex pore diameter of 70-150 μm. It was noted that Siltex pores lead to no "adhesive effect" (33).…”
Section: Surfacementioning
confidence: 99%
“…The Biocell surface is an aggressive, open-pore, textured surface, created with a lost-salt technique (28). The elastomeric shell is placed on a bed of finely graded salt, and light pressure is applied to increase the depth of the depressions.…”
Section: Chronic Inflammationmentioning
confidence: 99%